Pindara revisited - evolution and generic limits in Helvellaceae - K. Hansen; T. Schumacher; I. Skrede; S. Huhtinen; X.-H. Wang (RIJKSHERBARIUM, 2025)
The Helvellaceae encompasses taxa that produce some of the most elaborate apothecial forms, as well as hypogeous ascomata, in the class Pezizomycetes (Ascomycota). While the circumscription of the Helvellaceae is clarified, evolutionary relationships and generic limits within the family are debatable. A robust phylogeny of the Helvellaceae, using an increased number of molecular characters from the LSU rDNA, RPB2 and EF-1 alpha gene regions (4 299 bp) and a wide representative sampling, is presented here. Helvella s.lat. was shown to be polyphyletic, because Helvella aestivalis formed a distant monophyletic group with hypogeous species of Balsamia and Barssia. All other species of Helvella formed a large group with the enigmatic Pindara (/Helvella) terrestris nested within it. The ear-shaped Wynnella constitutes an independent lineage and is recognised with the earlier name Midotis. The clade of the hypogeous Balsamia and Barssia, and H. aestivalis is coherent in the three-gene phylogeny, and considering the lack of phenotypic characters to distinguish Barssia from Balsamia we combine species of Barssia, along with H. aestivalis, in Balsamia. The closed/tuberiform, sparassoid H. astieri is shown to be a synonym of H. lactea; it is merely an incidental folded form of the saddle-shaped H. lactea. Pindara is a sister group to a restricted Helvella, i.e., excluding the /leucomelaena lineage, on a notably long branch. We recognise Pindara as a separate genus and erect a new genus Dissingia for the /leucomelaena lineage, viz. H. confusa, H. crassitunicata, H. leucomelaena and H. oblongispora. Dissingia is supported by asci that arise from simple septa; all other species of Helvellaceae have asci that arise from croziers, with one exception being the /alpina-corium lineage of Helvella s. str. This suggests ascus development from croziers is the ancestral state for the Helvellaceae and that ascus development from simple septa has evolved at least twice in the family. Our phylogeny does not determine the evolutionary relationships within Helvella s. str., but it is most parsimonious to infer that the ancestor of the helvelloids produced subsessile or shortly stipitate, cup-shaped apothecia. This shape has been maintained in some lineages of Helvella s. str. The type species of Underwoodia, Underwoodia columnaris, is a sister lineage to the rest of the Helvellaceae.